Delayed Bronchopleural Fistula Formation Following Salvage Surgery of Stage IV Anaplastic Lymphoma Kinase-Positive Non-Small-Cell Lung Cancer - Lauren Barter; Stephanie Snow; Aneil Mujoomdar; Lara Best; Daniel French (Current Oncology)
This case report highlights the management of a delayed bronchopleural fistula (BPF) following salvage pulmonary resection to achieve local control and no radiographic evidence of disease in a patient treated with serial tyrosine kinase inhibitors (TKIs) for stage IV anaplastic lymphoma kinase (ALK)-positive non-small-cell lung cancer (NSCLC). The initial pulmonary resection was complicated by dense adhesions and an abnormally torturous pulmonary artery. Six weeks after the index surgery, the patient presented with a delayed BPF requiring decortication, repair of airway, and coverage of the bronchial stump with a serratus anterior muscle flap.